Extremely low-chlorine activated carbon and method for producing the same
Patent Information
- Application Number
- CN202611402016.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-13
AI Technical Summary
[0017]为解决现有活性炭无法深度脱氯、深度脱氯易造成碘吸附性能下降、化学方法易引入新杂质的技术问题,本发明提供了一种能在温和条件下,高效、无损地脱除活性炭中所有形态氯元素的方法,将硝酸氧化、胺化接枝、酸处理脱氯构建为一条完整的化学转化链条,利用硝酸的双重作用(清洗+表面化学改造),通过三步化学反应实现活性炭的超深度脱氯;通过本方法所制得的极低氯活性炭中氯元素的总含量控制在1ppm以下
[0039]同时,整个制备全程最高温度不超过,有效避免了高温对活性炭孔隙结构的破坏,解决了高温脱氯工艺导致活性炭吸附性能劣化的技术难题。整个工艺不涉及银离子等重金属的使用,不引入新的难去除杂质,试剂成本低,工艺条件温和,是一种绿色环保的活性炭深度纯化方法。
Smart Images

Figure SMS_117 
Figure SMS_122 
Figure SMS_127
Abstract
Description
Technical Field
[0001] This invention belongs to the field of activated carbon preparation and purification technology, specifically relating to an ultra-low chlorine activated carbon with a total chlorine content of less than 1 ppm and its preparation method. It is mainly used in fields with extremely high requirements for impurity content, such as the refining of electronic-grade chemicals, electrode materials for supercapacitors, and standard substances. Background Technology
[0002] Activated carbon, a carbon material with a well-developed pore structure and a large specific surface area, is widely used in adsorption separation, catalyst support, and electrochemical energy storage. With the development of the electronics industry and high-end manufacturing, the requirements for the purity of activated carbon are becoming increasingly stringent, especially the chlorine content, which has become one of the key indicators restricting its application in high-end fields. Applications such as electronic-grade chemical refining, high-purity gas purification, and supercapacitors require the total chlorine content in activated carbon to be below 1 ppm, a requirement that existing commercial activated carbon products struggle to meet.
[0003] The sources of chlorine in activated carbon are mainly twofold: firstly, residual chlorine compounds from the raw materials themselves; and secondly, the acid washing process using hydrochloric acid to remove metallic impurities during activated carbon purification. Even after repeated washing, chloride ions remain deep within the pores of hydrochloric acid-treated activated carbon due to the capillary effect, making complete removal extremely difficult. Furthermore, during the preparation or acid washing process, chlorine may form chemically bound chlorine bonds (C-Cl covalent bonds) on the carbon skeleton surface, which cannot be broken and removed by conventional washing. This chemically bound chlorine is the key bottleneck restricting the reduction of chlorine content in activated carbon to below 1 ppm.
[0004] Existing technologies for removing chlorine from activated carbon can be mainly categorized as follows:
[0005] (1) Physical washing method: Activated carbon is repeatedly washed with deionized water or pure water, which can only remove free chloride ions. It is almost ineffective for physically adsorbed chlorine and chemically bound chlorine (C-Cl bond) deep in the micropores, and the water consumption is large and the cycle is long.
[0006] (2) Chemical displacement method: Chemical reagents are used to displace chloride ions, but the process is complicated and may introduce new impurities such as sodium, potassium, and silver, which increases the difficulty of subsequent purification.
[0007] (3) High temperature heat treatment method: decomposes chlorine-containing functional groups at high temperature, but the energy consumption is high. High temperature may cause carbon skeleton shrinkage, pore structure collapse, and adsorption performance is severely degraded.
[0008] Specifically, the relevant technologies disclosed in existing publicly available patents and their limitations are as follows:
[0009] Patent document CN109574006A discloses a process for preparing low-iron, low-chlorine activated carbon. The process involves raw material selection, acid washing, primary rinsing, ammonia removal of impurity ions, secondary rinsing, drying, and secondary iron removal. This process primarily removes chlorine through complexation sedimentation and physical rinsing, but its ability to remove chemically bound chlorine deep within micropores is limited. The final product only meets the requirement of "extremely low chlorine precipitation in water," and it is unclear whether it can reduce the total chlorine content of the activated carbon to below 1 ppm. Furthermore, the use of ammonia may introduce new nitrogenous impurities, and the process is cumbersome and has a long production cycle.
[0010] International patent US5972834A discloses a method for thermal dehalogenation of halogenated activated carbon in a hydrogen-containing gas (hydrogen, water vapor, or lower hydrocarbons). The following treatment can "almost completely eliminate" chlorine from activated carbon. However, this method requires... Under high-temperature conditions, the carbon skeleton of activated carbon shrinks significantly, the microporous structure collapses, resulting in a substantial loss of specific surface area and severe deterioration of adsorption performance. Furthermore, high-temperature operation involves high energy consumption, large equipment investment, and numerous safety hazards, which does not meet the requirements of green and low-carbon development.
[0011] In summary, the existing technologies share the following common shortcomings:
[0012] Defect 1: It is impossible to stably control the total chlorine content of the activated carbon to below 1 ppm, thus failing to achieve deep dechlorination of ultra-low chlorine activated carbon;
[0013] Defect 2: High-temperature dechlorination leads to a significant decrease in specific surface area and iodine adsorption performance, resulting in severe deterioration of adsorption performance;
[0014] Defect 3: Physical methods cannot remove chemically bound chlorine ( covalent bond);
[0015] Fourthly, chemical methods may introduce new impurities, increasing the difficulty of subsequent processing.
[0016] Therefore, developing a method that can efficiently and non-destructively remove all forms of chlorine, including chemically bound chlorine, from activated carbon under mild conditions has significant industrial value and is an urgent practical need. Summary of the Invention
[0017] To address the technical problems of existing activated carbon's inability to deeply dechlorinate, the tendency of deep dechlorination to cause a decline in iodine adsorption performance, and the easy introduction of new impurities by chemical methods, this invention provides a method for efficiently and non-destructively removing all forms of chlorine from activated carbon under mild conditions. It constructs a complete chemical transformation chain by integrating nitric acid oxidation, amination grafting, and acid treatment dechlorination. Utilizing the dual effects of nitric acid (cleaning + surface chemical modification), ultra-deep dechlorination of activated carbon is achieved through a three-step chemical reaction. The total chlorine content in the ultra-low chlorine activated carbon obtained by this method is controlled below 1 ppm.
[0018] To achieve the above objectives, the technical solution adopted in this invention is: an extremely low chlorine activated carbon, with a total chlorine content of less than 1 ppm and an iodine adsorption value of... Specific surface area .
[0019] Among them, the preferred total chlorine content .
[0020] A method for preparing ultra-low chlorine activated carbon, the specific steps of which are as follows:
[0021] Step 1, Nitric Acid Oxidation Pretreatment: The activated carbon raw material is crushed, ground, and sieved to... The object is placed in a mass fraction of In a nitric acid solution, activated carbon and nitric acid solution are mixed at a solid-liquid ratio. Mix, in Bottom stirring treatment This process allows activated carbon to undergo surface oxidation modification while removing ash, introducing oxygen-containing functional groups such as carboxyl groups; after filtration, it is rinsed with ultrapure water (resistivity...) Rinse until the pH of the washing solution is [value missing]. .
[0022] In step one, the nitric acid oxidation treatment plays a dual role: firstly, it removes ash and some metallic impurities from the activated carbon, opening up blocked pores; secondly, it introduces a large number of carboxyl groups onto the surface of the activated carbon and at the pore openings. Functional groups. These carboxyl groups serve as covalent anchors for subsequent chemical reactions, enabling the amination reagent to be firmly grafted onto the carbon skeleton surface via covalent bonds, fundamentally avoiding the problem of easy amine group detachment caused by physical mixing. Simultaneously, nitric acid oxidation selectively acts on the activated carbon surface and open pores without damaging the graphite microcrystalline structure within the carbon skeleton, laying the material foundation for achieving deep dechlorination under mild conditions.
[0023] Preferably, in step one, the mass fraction of the nitric acid solution is: The processing temperature is .
[0024] Step 2, Amination Grafting: Impregnate the pretreated activated carbon obtained in Step 1 with a mass fraction of In the aqueous solution of the amination reagent, the solid-liquid ratio is ,exist Stirred reaction This allows the amine groups to be covalently grafted onto the carboxyl sites on the activated carbon surface via amide bonds. After the reaction is complete, the mixture is filtered, and the solid-liquid ratio is... Ultrapure water rinsing Next, remove residual amination reagents physically adsorbed on the surface;
[0025] In step two, the amination reagent is A mixture of one or more aliphatic polyamines and aromatic polyamines.
[0026] Preferably, the amination reagent is one or any combination of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and p-phenylenediamine.
[0027] In this step, the amination grafting treatment utilizes the amidation reaction between carboxyl and amino groups to covalently fix the amino groups onto the activated carbon surface via chemical bonds. The grafted amino groups provide abundant basic sites, which can be converted into ammonium cations under subsequent acidic conditions. Thus obtaining the chloride ion Its electrostatic trapping ability. This chemical modification strategy removes substances that traditional methods cannot eliminate. Bonded chlorine is transformed into removable ionic chlorine through subsequent chemical transformation, providing a key prerequisite for ultra-deep dechlorination.
[0028] Step 3, Acid Treatment for Dechlorination: The amination-grafted activated carbon obtained in Step 2 is impregnated with an acid solution containing a mass fraction of [missing information]. In a dilute nitric acid or dilute sulfuric acid solution, the solid-liquid ratio is... Stir at room temperature After filtration, the activated carbon is thoroughly rinsed with ultrapure water until the washing solution is confirmed to be free of chloride ions by methods known in the art. The rinsed activated carbon is then... Drying This yields an ultra-low chlorine activated carbon product with a total chlorine content of less than 1 ppm.
[0029] This step is the key to achieving ultra-deep dechlorination in this invention, in which the following three synergistic processes occur simultaneously:
[0030] First, protonation activation: grafted amine groups Under dilute acid conditions, it gains protons and transforms into ammonium cations. The surface positive charge density increases significantly, which has an effect on Its electrostatic attraction ability is significantly enhanced.
[0031] second, Bond breaking: An acidic environment can effectively promote the breaking of residual bonds in activated carbon. The covalent bond undergoes hydrolytic breakage, releasing... This process cannot be achieved under traditional neutral water washing or alkaline conditions.
[0032] Third, in-situ capture: Bond breakage releases Within the micropores, the diffusion distance is extremely short, and the ammonium cations are immediately captured by neighboring ammonium cations through electrostatic interactions, forming water-soluble ammonium salts. .
[0033] The three processes mentioned above are highly coupled in both space and time: Bond breakage and release With ammonium cation capture It happened almost simultaneously, effectively avoiding Re-adsorption occurs deep within the micropores. Ultimately, both chemically bound and physically adsorbed chlorine are uniformly converted into water-soluble ammonium salts, which can then be completely removed by subsequent water washing.
[0034] The three-step reaction forms a complete logical chain in terms of chemical mechanism, and none of them can be omitted:
[0035] Step 1 (nitric acid oxidation) introduces carboxyl anchor sites, providing reaction sites for subsequent covalent grafting;
[0036] Step 2 (Amination Grafting) involves covalently fixing amine groups via amide bonds to construct chloride ion trapping sites;
[0037] Step 3 (Acid Treatment Dechlorination) Breakage L-bonding, protonation activation of amine groups, in-situ capture and release .
[0038] There is a clear causal relationship between the three steps: without the carboxyl anchor in step one, the amine group in step two cannot be firmly grafted by covalent bonds (it can only be physically adsorbed and easily detached in subsequent steps); without the covalently grafted amine group in step two, an effective [agent / method] cannot be formed in step three. Capture sites; if there is no acid treatment in step three, The bonds cannot be broken, the chemically bound chlorine cannot be released, and the amino groups cannot be converted into ammonium cations with strong electrostatic capture capabilities; the synergistic effect of the three together achieves an ultra-deep dechlorination effect with a chlorine content that is stably below 1 ppm.
[0039] Meanwhile, the highest temperature throughout the entire preparation process does not exceed This method effectively avoids the damage to the pore structure of activated carbon caused by high temperatures, solving the technical problem of deterioration in the adsorption performance of activated carbon caused by high-temperature dechlorination processes. The entire process does not involve the use of heavy metals such as silver ions, does not introduce new difficult-to-remove impurities, has low reagent costs, and mild process conditions, making it a green and environmentally friendly method for deep purification of activated carbon.
[0040] Compared with the prior art, the specific beneficial effects of the present invention are reflected in:
[0041] I. Ultra-low chlorine content: This invention, through a three-step chemical conversion chain, can stably control the total chlorine content of activated carbon to below 1 ppm, with a minimum of [missing value]. It meets the stringent requirements of ultra-low chlorine activated carbon in high-end applications such as electronic-grade chemical refining and standard sample production.
[0042] II. Excellent adsorption performance is maintained: the process temperature does not exceed [a certain value] throughout the entire process. This avoids carbon skeleton shrinkage and micropore collapse caused by high temperatures, and the product's iodine adsorption value retention rate can reach [percentage missing]. The above-mentioned specific surface area retention rate can reach The above solutions address the industry-wide problem of severe adsorption performance degradation caused by high-temperature dechlorination, achieving a balance between deep dechlorination and performance maintenance.
[0043] III. Highly efficient removal of chemically bound chlorine: under acidic conditions The hydrolytic breaking of bonds and the in-situ capture of ammonium cations have solved the technical bottleneck of traditional physical washing methods being unable to remove chemically bound chlorine.
[0044] IV. No new impurities introduced: Using nitric acid, polyamines and dilute acids as treatment reagents, it does not involve heavy metals such as silver and mercury, and does not introduce new difficult-to-remove impurities. It is suitable for activated carbon from different raw material sources such as coconut shell and coal. The reagent cost is low and the process is green and environmentally friendly.
[0045] V. Mild process conditions: The entire process is conducted at atmospheric pressure and does not exceed [a certain value]. It operates under suitable conditions, has low equipment requirements, low energy consumption, high safety, and is easy to scale up industrially. Detailed Implementation
[0046] To make the technical problems, solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0047] Methods for detecting chlorine content: The total chlorine content of activated carbon products is determined using a combustion-ion chromatography method known in the art. Specifically, the activated carbon sample is fully combusted in an oxygen bomb, converting chlorine into an absorbable ionic form. After absorption by the absorbent, quantitative analysis is performed using ion chromatography. This method can accurately determine the total chlorine content in activated carbon at levels of ppm and below. The detection of chloride ions in the washing solution uses the silver nitrate turbidimetric method or ion chromatography, both known in the art, to confirm the washing endpoint.
[0048] Example 1
[0049] A method for preparing ultra-low chlorine activated carbon, using commercially available coconut shell-based granular activated carbon (iodine value...) Specific surface area chlorine content Using [material name] as raw material, crush, grind, and sieve to 325 mesh. Take 100g of the sieved activated carbon and place it in a 500mL container with a mass fraction of [missing information]. In nitric acid solution (solid-liquid ratio) ,exist After stirring for 4 hours, the mixture was filtered and then treated with ultrapure water (resistivity 100%). Rinse until the pH of the washing solution is 6.8.
[0050] The pretreated activated carbon was impregnated in 1000 mL of water with a mass fraction of [missing value]. In an aqueous solution of ethylenediamine (solid-liquid ratio) ,exist The mixture was stirred and reacted for 5 hours. After the reaction was complete, it was filtered, and the solid-liquid ratio was used. Rinse three times with ultrapure water to remove residual amination reagents from the surface.
[0051] The above-mentioned amination activated carbon was then impregnated in 500 mL of water with a mass fraction of In dilute nitric acid solution (solid-liquid ratio) ), room temperature ( Stir for 30 minutes. After filtration, rinse thoroughly with ultrapure water until no chloride ions are detected in the washings by silver nitrate turbidimetric assay. After drying for 6 hours, the ultra-low chlorine activated carbon product is obtained.
[0052] The product performance test results of this embodiment are shown in Table 1.
[0053] Example 2
[0054] Commercially available coconut shell-based granular activated carbon (iodine value) Specific surface area Using activated carbon (chlorine content 180ppm) as raw material, it is crushed, ground, and sieved to 325 mesh. 100g of the sieved activated carbon is placed in 300mL of a solution containing 180ppm chlorine. In nitric acid solution (solid-liquid ratio) ),exist The mixture was stirred for 4 hours, filtered, and then rinsed with ultrapure water until the pH of the washing solution was 6.5.
[0055] The pretreated activated carbon was impregnated in 500 mL of water with a mass fraction of [missing value]. In triethylenetetramine aqueous solution (solid-liquid ratio) ),exist The mixture was stirred and reacted for 5 hours. After the reaction was complete, it was filtered, and the solid-liquid ratio was used. Rinse three times with ultrapure water to remove residual amination reagents from the surface.
[0056] The remaining acid treatment and dechlorination steps are the same as in Example 1.
[0057] The product performance test results of this embodiment are shown in Table 1.
[0058] Example 3
[0059] Commercially available coal-based activated carbon (iodine value) Specific surface area Using activated carbon (chlorine content 220ppm) as raw material, it is crushed, ground, and sieved to 200 mesh. 100g of the sieved activated carbon is placed in a 400mL container with a mass fraction of... In nitric acid solution (solid-liquid ratio) ),exist The mixture was stirred for 3 hours, filtered, and then rinsed with ultrapure water until the pH of the washing solution was 7.0.
[0060] The pretreated activated carbon was impregnated in 800 mL of water with a mass fraction of [missing value]. In diethylenetriamine aqueous solution (solid-liquid ratio) ),exist The mixture was stirred and reacted for 6 hours. After the reaction was complete, it was filtered, and the solid-liquid ratio was used. Rinse twice with ultrapure water to remove residual amination reagents from the surface.
[0061] The above-mentioned amination activated carbon was then impregnated in 500 mL of water with a mass fraction of In dilute sulfuric acid solution (solid-liquid ratio) ), room temperature ( Stir for 20 minutes. After filtration, rinse thoroughly with ultrapure water until no chloride ions are detected in the washings. After drying for 5 hours, the ultra-low chlorine activated carbon product is obtained.
[0062] The three-step synergistic mechanism constitutes a complete technological closed loop: nitric acid oxidation introduces carboxyl anchor points (the basis of covalent grafting). Amination grafting covalently fixes amino groups (constructing capture sites). Acid treatment fracture Key and capture in place (To achieve complete elimination). The three steps are closely related by cause and effect, each is indispensable, and they produce a synergistic effect.
[0063] The product performance test results of this embodiment are shown in Table 1.
[0064] Example 4
[0065] Commercially available coconut shell-based granular activated carbon (iodine value) Specific surface area Using activated carbon (chlorine content 180ppm) as raw material, it is crushed, ground, and sieved to 325 mesh. 100g of the sieved activated carbon is placed in a 500mL container with a mass fraction of... In nitric acid solution (solid-liquid ratio) ),exist After stirring for 2 hours, filter and rinse with ultrapure water until the pH of the washing solution is [value missing]. .
[0066] The pretreated activated carbon was impregnated in 1000 mL of water with a mass fraction of [missing value]. In tetraethylenepentamine aqueous solution (solid-liquid ratio) ),exist The mixture was stirred and reacted for 4 hours. After the reaction was complete, it was filtered, and the solid-liquid ratio was used. Rinse three times with ultrapure water to remove residual amination reagents from the surface.
[0067] The remaining acid treatment and dechlorination steps are the same as in Example 1 (using...) Dilute nitric acid).
[0068] The product performance test results of this embodiment are shown in Table 1.
[0069] Comparative Example 1
[0070] Using the same coconut shell-based granular activated carbon as in Example 1, only conventional nitric acid washing was performed (the activated carbon was placed in 500 mL of water with a mass fraction of...). In nitric acid solution, The mixture was stirred for 4 hours and rinsed with ultrapure water, without undergoing amination grafting or acid treatment for dechlorination.
[0071] The product performance test results are shown in Table 1.
[0072] Comparative Example 2
[0073] Using the same coconut shell-based granular activated carbon as in Example 1, after nitric acid washing and ultrapure water rinsing, only amination grafting treatment was performed (the activated carbon was immersed in 1000 mL of water with a mass fraction of...). In an aqueous solution of ethylenediamine, The mixture was stirred and reacted for 5 hours. No acid treatment or dechlorination step was performed; the mixture was washed only with ultrapure water.
[0074] The product performance test results are shown in Table 1.
[0075] Comparative Example 3
[0076] Using the same coconut shell-based granular activated carbon as in Example 1, without nitric acid oxidation pretreatment, the same amination grafting as in Example 1 was directly performed (the activated carbon was impregnated in 1000 mL of water with a mass fraction of...). In an aqueous solution of ethylenediamine, (Stirred reaction for 5 hours) and acid treatment for dechlorination (impregnating amination activated carbon in water with a mass fraction of 1000 kJ / kg) (The solution was treated by stirring at room temperature for 30 minutes in a dilute nitric acid solution.)
[0077] The product performance test results are shown in Table 1.
[0078] Comparative Example 4
[0079] Using the same coconut shell-based granular activated carbon as in Example 1, and following the method disclosed in patent US5972834A, under a nitrogen atmosphere... Heat treatment for 4 hours. Product performance test results are shown in Table 1.
[0080] Table 1. Performance parameters of raw materials and products from each example and comparative example.
[0081]
[0082] Note: Chlorine content was determined using combustion-ion chromatography; iodine value was determined according to... Specific surface area is determined by... (BET method) determination. Iodine retention rate = product iodine value iodine value of raw materials Specific surface area retention rate = Product specific surface area / Raw material specific surface area × 100%.
[0083] Table 2 Characterization of surface functional groups of products at each step (XPS analysis, Example 1)
[0084]
[0085] Note: XPS analysis uses monochrome. X-rays were used as the excitation source. The data in the table are presented as relative trends: Carboxyl groups after nitric acid oxidation in step one... ester group The peak area increased significantly, indicating the successful introduction of oxygen-containing functional groups; the peak area of N element increased significantly after the diamine grafting step, and at the same time... The corresponding decrease in peak area indicates that the amino group was successfully covalently grafted to the carboxyl site through the amide bond; after acid treatment and dechlorination in step three, the surface Cl signal dropped below the detection limit, indicating that the chlorine element was efficiently removed.
[0086] Table 3 Comparative Analysis of the Invention and the Prior Art
[0087]
[0088] Results analysis, based on the data in Tables 1 and 3, shows that:
[0089] I. The chlorine content in Examples 1-4 is all lower than The iodine retention rate was all within The above specific surface area retention rates are all within [percentage missing]. The above demonstrates that the method of the present invention can stably prepare chlorine-containing... The activated carbon exhibits extremely low chlorine content while maintaining excellent adsorption performance. In Example 3, coal-based activated carbon was used as the raw material, achieving an ultra-low chlorine content of 0.7 ppm, demonstrating the universality of the method for activated carbon from different raw material sources.
[0090] II. Comparative Example 1 (nitric acid washing only, no amination grafting and acid treatment for dechlorination) had a chlorine content of 15.6 ppm, which is much higher than that of Example 1 (0.6 ppm), indicating that nitric acid washing alone can only remove some free chlorine and ash, and cannot achieve deep dechlorination.
[0091] III. Comparative Example 2 (nitric acid oxidation + amination grafting, dechlorination without acid treatment) had a chloride content of 8.3 ppm, which, although lower than Comparative Example 1 (after amination grafting, the amino groups can adsorb some chloride ions through weak coordination), was still much higher than 1 ppm. This indicates that without the acid treatment step, The bonds cannot be effectively broken, and the chemically bound chlorine is difficult to remove; at the same time, the amine group is not protonated, which hinders the removal of chlorine. The limited capture capacity fully demonstrates the necessity of the acid treatment dechlorination step.
[0092] IV. Comparative Example 3 (no nitric acid oxidation, direct amination grafting + acid treatment for dechlorination) had a chlorine content as high as 25.1 ppm, even higher than Comparative Example 1. This indicates that without the carboxyl anchor points introduced by nitric acid oxidation, the amino groups cannot be firmly grafted onto the activated carbon surface via covalent bonds, but can only adhere by physical adsorption. A large number of these groups detach during subsequent acid treatment and water washing, resulting in poor dechlorination and even introducing additional impurities due to residual amination reagent. This fully demonstrates the fundamental role of nitric acid oxidation pretreatment in constructing covalent graft anchor points and also proves that simple physical impregnation amination cannot replace the covalent grafting strategy of this invention.
[0093] V. Comparative Example 4 (High Temperature Method) The chlorine content of the sample was 2.1 ppm, which was significantly lower than that of the raw material, but still not below 1 ppm, and the iodine retention rate was only [missing information]. The specific surface area retention rate is only The adsorption performance is severely degraded, which further highlights the significant advantage of the mild conditions process of the present invention in maintaining adsorption performance.
[0094] VI. Three-step synergistic effect verification: Comparative Examples 1, 2, and 3 were respectively lacking amination grafting. The three key steps of acid treatment dechlorination, acid treatment dechlorination, and nitric acid oxidation had chlorine contents of 15.6 ppm, 8.3 ppm, and 25.1 ppm, respectively, all significantly higher than those in Example 1 (0.6 ppm). This comparison fully demonstrates that each of the three chemical steps is indispensable; only through their synergistic effect can an ultra-low chlorine level of <1 ppm be achieved, resulting in… The synergistic effect.
[0095] The XPS analysis results in Table 2 further confirm the chemical mechanism of this invention at the molecular level: oxidation with nitric acid significantly increases the number of oxygen-containing functional groups; amination grafting significantly increases the N content while correspondingly decreasing the content of oxygen-containing functional groups; and acid treatment for dechlorination reduces the surface Cl content below the detection limit. This series of characterization data provides direct evidence for the technical concept of a three-step chemical transformation.
[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the scope of the present invention.
Claims
1. A type of extremely low-chlorine activated carbon, characterized in that, Total chlorine content Iodine adsorption value Specific surface area .
2. The ultra-low chlorine activated carbon according to claim 1, characterized in that, Total chlorine content .
3. A method for preparing the ultra-low chlorine activated carbon as described in claim 1, characterized in that, The specific steps are as follows: Step 1, Nitric Acid Oxidation Pretreatment: The activated carbon raw material is crushed, ground, and sieved to... The object is placed in a mass fraction of In nitric acid solution, according to solid-liquid ratio Mix, in Bottom stirring treatment h, after filtration, rinse with ultrapure water until the pH of the washing solution is [value missing]. ; Step 2, Amination Grafting: Impregnate the pretreated activated carbon with a mass fraction of In the aqueous solution of the amination reagent, the solid-liquid ratio is ,exist Stirred reaction After the reaction is complete, filter and use a solid-liquid ratio of... Ultrapure water rinsing Next, remove residual amination reagents physically adsorbed on the surface; Step 3, Acid Treatment for Dechlorination: The amination-grafted activated carbon obtained in Step 2 is impregnated in a 0.05%-1% (w / w) dilute nitric acid or dilute sulfuric acid solution, with a solid-liquid ratio of [missing value]. Stir at room temperature After filtration, the activated carbon is thoroughly rinsed with ultrapure water until no chloride ions are detected in the washing solution. The rinsed activated carbon is then... Drying h, that is, an activated carbon product with a total chlorine content of less than 1 ppm.
4. The method for preparing ultra-low chlorine activated carbon as described in claim 3, characterized in that, In step one, the mass fraction of the nitric acid solution is: The processing temperature is .
5. The method for preparing ultra-low chlorine activated carbon as described in claim 4, characterized in that, In step two, the amination reagent is A mixture of one or more aliphatic polyamines and aromatic polyamines.
6. The method for preparing ultra-low chlorine activated carbon as described in claim 5, characterized in that, The amination reagent is one or any combination of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and p-phenylenediamine.
Citation Information
Patent Citations
Preparation process of low-iron low-chlorine active carbon
CN109574006A
Carbon adsorbent, manufacturing method therefor, gas separation method and device therefor
US5972834A